The value-added tax : Hearings before the Joint Economic Committee Congress Of the United States, Ninety-second Congress, second session - United States. Congress. Joint Economic Committee (Washington, D.C. U.S. Govt. Print. Off., 1972)
Explores what the new value-added tax is, how much revenue it can raise, how equitable it is as a source of Federal funds.
Hearings held Mar. 21-24, 1972.
Includes bibliographical references.
oif 05/03/2019
Loans
Keywords: Value-added tax--Law and legislation; United States